Enhancing Elementary Students’ Mathematics Achievement through Problem-Based Learning Integrated with “Talintar” Smart Multiplication Table Media - Suryani, Suryani; M. Ridwan, M. Ridwan; Hardiansyah, Framz (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aimed to improve elementary students’ mathematics achievement through the integration of the Problem-Based Learning (PBL) model and Talintar (Smart Multiplication Table) media. A Classroom Action Research (CAR) design was implemented in two cycles involving 21 fourth-grade students at SDN Sapeken VIII, Sumenep, Indonesia. Each cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through written tests, classroom observations, and documentation, then analyzed using descriptive quantitative methods. Results indicated a steady improvement in learning outcomes, with the mean score rising from 57.57 in the pre-cycle to 68.48 in Cycle I and 85.90 in Cycle II. The proportion of students achieving the mastery criterion (≥70) increased from 19% to 100%, yielding an N-gain of 0.67 (medium-to-high improvement) and a large effect size (d ≈ 2.3). Qualitative observations revealed higher engagement, motivation, and confidence among students during the intervention. The findings confirm that integrating PBL with Talintar media effectively enhances conceptual understanding, problem-solving ability, and student participation. This model demonstrates that combining inquiry-based pedagogy with contextual visual media offers a sustainable and scalable approach to improving mathematics learning within Indonesia’s Kurikulum Merdeka framework.